Extralabel mastitis theraphy: what does it mean? - Roberson, J.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Extra-label drug use (ELDU) is needed to provide optimal therapy for ill dairy cattle. Proper ELDU requires cooperation and compliance between the veterinarian and producer to ensure that proper drug withdrawal times are observed.
Keywords: Dairy; Regulations; Mastitis